2008
DOI: 10.1007/s10194-008-0051-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving care through health economics analyses: cost of illness and headache

Abstract: The impact of headache disorders is a problem of enormous proportions, both for individual and society. The medical literature tried to assess its effects on individuals, by examining prevalence, distribution, attack frequency and duration, and headache-related disability, as well as effects on society, looking at the socio-economic burden of headache disorders [Rasmussen (Cephalalgia 19:20–23, 1999)]; [Lanteri-Minet et al. (Pain 102:143–149, 2003)]. The issue of costs represents an important problem too, conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 24 publications
(32 reference statements)
0
50
0
1
Order By: Relevance
“…However, since dizziness is such a commonly encountered symptom [6,15,17], both in the population, primary care and secondary care [17], this finding highlights the potential global economic impact of dizziness on European society as a whole. Again, although attempts have been made in the headache literature to quantify such impacts in the form of health economics analyses [13], the economic impact of dizziness remains unknown and deserves to be researched.…”
mentioning
confidence: 99%
“…However, since dizziness is such a commonly encountered symptom [6,15,17], both in the population, primary care and secondary care [17], this finding highlights the potential global economic impact of dizziness on European society as a whole. Again, although attempts have been made in the headache literature to quantify such impacts in the form of health economics analyses [13], the economic impact of dizziness remains unknown and deserves to be researched.…”
mentioning
confidence: 99%
“…[3][4][5][8][9][10][11][12][13][14][15][16] Nevertheless, there is debate as to the proportional contribution of absenteeism compared to presenteeism, with the latter gaining more attention over the years. 3,8,[16][17][18][19][20][21][22][23][24] The American Migraine Study revealed that 51% of women and 38% of men experienced six or more lost workday equivalents each year as a result of migraine attacks, two-thirds of which were attributed to reduced effectiveness at work rather than to actual absenteeism. 12 Meanwhile, Hu et al 8 found missed workdays to outnumber lost workday-equivalents for female migraine sufferers (68.9 million missed days vs 41.6 million lost work-equivalents), though not for males.…”
mentioning
confidence: 99%
“…In addition to the direct consequences on individual patients, physicians' fondness for instrumental investigations is also a public health problem and a cause of inappropriate use of economic resources [24,25]. The cost of migraine in Europe is estimated at EUR 27 billion annually [25,26]. However, the total cost should be diversified according with the migraine type.…”
Section: Discussionmentioning
confidence: 99%